Potensi serangga pengunjung bunga sebagai vektor penyakit darah bakteri (Ralstonia solanacearum Phylotipe IV) pada pisang di Sumatera Barat - Mairawita Mairawita; Trimurti Habazar; Ahsol Hasyim; Nasril Nasir; Suswati Suswati (Jurnal Entomologi Indonesia, 2012)
Blood diseases caused by Ralstonia solancearum Phylotype IV is a major cause of production loss of banana in Indonesia, particularly for areas in West Sumatera. Currently there is a lack of information on blood diseases. The objective of this study was to obtain data of insect diversity and its potential as a dissemination agent of R. solanacearum Phylotype IV in West Sumatera. This research was conducted with a purposive sampling method in the Tabek Panjang highlands, District of Baso, Agam Regency and Pasar Usang lowland, district of Batang Anai, Pariaman Regency, West Sumatera. The results showed that banana plants infected by R. solanacearum Phylotype IV have a high diversity of flower-visiting insects. The diversity of insects in the lowlands is higher than that in highland and mainly are dominated by Trigona spp. (Hymenoptera: Apidae), Drosophila sp. (Diptera: Drosophilidae). To test the potential of both insect as vector of the blood diseases, isolated and identification of the bacteria using triphenyl tetrazolium medium chlorid (TTC) was used. Result showed that bacteria isolated from both insect are R. solanacearum hence providing evidence of the insect as vector of the blood diseases. Both insects have the potential to be vector of R. solanacearum Phylotype IV in West Sumatera. The identification of the bacteria that causes the disease. The identification of bacteria that is spread by flower visitors insects are R.solanacearum Phylotipe IV.